Ranah Domestik adalah Milik Bersama: Gender Equilibrium dalam Kartun Youtube “Bayi John” - Zakridatul Agusmaniar Rane (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Baby John is the YouTube content consisting of songs and videos that represent different messages. The songs tell direct messages about daily activities like brushing their teeth, washing hands, etc., while the video has an implied message about gender roles in the domestic sphere. This research investigated how the message of gender equilibrium is represented in a YouTube cartoon for toddlers, "Baby John." This research uses the descriptive qualitative method and gender equilibrium theory as its foundation. This study found that there is equality between father and mother, as well as between sister and brother, in domestic work. The family members are in a mutual cooperation and complementarity relationship. Men's participation in domestic work is considered to create a partnership between men and women, which is termed gender equilibrium. Introducing it to children as early as possible will influence their views about gender equality. The message of gender equilibrium is conveyed straightforwardly and in a simple way so the children can immediately imitate it. Thus, the rapid transfer of ideology, knowledge, and habits from the video to children is possible.